Playful corners and its methodological didactic influence in the teaching-learning process in Initial Education - Jéssica Lourdes Arteaga Mera, Lubis Carmita Zambrano Montes (International Journal of Advanced Science and Technology, 2020)
In order to achieve meaningful learning, children need to be protagonists in the development of their own abilities and skills; In initial education, this role can be achieved through different routes, among which creative games and playful activities stand out. However, in some institutions the application of traditional methods with limited contribution to the development of skills of infants persists. The objective of this article is to identify the usefulness of playful corners in the didactic actions of the teacher to favor exploration, discovery, and children's creative thinking activities. The methodology is bibliographic and analysis-synthesis, induction-deduction were used as theoretical methods; modeling was also used for the design of didactic-methodological actions for the treatment of recreational corners in the teaching-learning process at the initial level. The research process made it possible to demonstrate the relevance of play corners as a didactic means that enhances capacities in infants and that contributes to playing a leading role in their training process and the achievement of effective and lasting learning.